DEMOGRAPHIC INFLUX AND SECURITY CHALLENGES IN INDIA'S NORTHEAST - Meitei, Kangujam Sanatomba (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The Northeast has long grappled with the persistent challenge of large-scale illegal immigration from neighbouring countries. Driven by vote bank politics, inadequate regulatory mechanisms, and population pressure in Bangladesh, this influx has produced serious demographic imbalances and socio-economic strain on indigenous communities. The resulting tensions between locals and immigrants have frequently escalated into violent clashes, posing a recurring law and order problem for state governments. The marginalization of indigenous peoples has, in turn, fuelled protest movements and insurgencies in states like Assam and Tripura, thereby deepening internal security challenges. At the same time, the infiltration of extremist networks through these migration routes has posed grave external security concerns, with cross-border linkages amplifying the risks for India. India’s foreign policy missteps in Tibet and East Pakistan further shaped the demographic and political trajectory of the region. While Tibetan refugees have remained largely non-disruptive, the continuous influx from Bangladesh constitutes a major security challenge. Illegal immigration, therefore, must be understood not only as a regional issue but as a national concern that threatens both the internal stability and external security of India.